Assessing the impact of non-protein nitrogen or rumen undegradable protein supplementation on rumen bacterial diversity and ruminal fermentation in grazing steers during the dry season - Dias, Ana Veronica Lino; Granja-Salcedo, Yury Tatiana; Messana, Juliana Duarte; Camargo, Karine Dalla Vecchia; Alves, Kênia Larissa Gomes Carvalho; Machado, Elisabeth Victória Alves; Constancio, Milena Tavares Lima; Reis, Ricardo Andrade; Berchielli, Telma Teresinha (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to evaluate the effects of sources of non-protein nitrogen (NPN) or rumen undegradable protein (RUP) as supplements on intake, nutrient digestibility, fermentation parameters, and ruminal microbiota in Nellore steers grazing during the dry season.MethodsThe experiment was conducted during the dry season from September to October 2018, in a grazing area of Urochloa brizantha (A. Rich.) Stapf. cv. Xaraés. Eight rumen-and duodenum-cannulated Nellore steers were used in a 4 × 4 Latin square design (2 treatments and 2 periods) balanced for residual effects. The treatments included (1) mineral salt with urea (SMU), formulated to meet 50% of the steer RDP requirement as NPN; and (2) supplementation with corn gluten meal (GLU; 0.3% of body weight) as a source of RUP, with added mineral salt.ResultsGLU supplementation significantly increased supplement intake (p < 0.05) and tended to decrease the intake of forage NDF. Although GLU supplementation improved NDF digestibility, no significant differences were observed in the digestibility of DM, OM, or CP between the treatments (p > 0.05). GLU supplementation significantly increased the relative abundance of several genera, including Ruminococcus 1, Ruminococcus 2, Erysipelotrichaceae UCG-004, Thermoplasmatales Incertae Sedis, Lachnospiraceae XPB1014, Anaeroplasma spp., Anaerotruncus spp. and Eubacterium ruminantium (p < 0.05). The PCA biplot revealed positive associations between GLU supplementation and greater ruminal abundance of Prevotellaceae UCG-004 and Bacteroidetes, as well as with higher concentrations of butyrate, propionate, and valerate acids.DiscussionSupplementation with GLU as a source of RUP in grazing steers during the dry season modulated the rumen microbiota by increasing the abundance of key fibrolytic bacteria and improved fiber digestibility.